Relationship of omnichannel marketing and integrated communications in a Peruvian company - Santos Burgos , Victoria Del Pilar (2021)
The aim of this research was to determine the relationship between omnichannel marketing and integrated communications in the Footloose company, in Cajamarca, 2020. The population consisted of 120 000 people and the study sample, 383 clients. The technique used to collect data was the survey and the instrument used was the questionnaire for each of the variables, which was designed through the Likert scale. For the omnichannel marketing variable, a 5-level response scale made up of 25 questions was used and in the case of the integrated communications variable, a 5-level response scale made up of 18 questions was used. The type of study was basic, with qualitative data, with a descriptive-correlational level and a non-experimental design. It is concluded that there is a moderate positive relationship between omnichannel marketing and integrated communications.